ANALISIS PERILAKU KONSUMEN TERHADAP KEGIATAN TRANSAKSI ONLINE MENGGUNAKAN PENDEKATAN RED OCEAN STRATEGY & BLUE OCEAN STRATEGY - Sonata, Derry Aryandi; Hapsari, Yaning Tri (Universitas Muria Kudus, 2025)
This research aims to analyze consumer behavior towards online transaction activities using the Red Ocean Strategy and Blue Ocean Strategy approaches on the digital banking application